(untitled) (Research, Society and Development, 2021)
Mitra Swalayan Kartasura is a private company engaged in the retail sector to fulfill basic needs. This objective is to address the impact of satisfaction on commitment to organizational commitment, to respond to the significance of the impact of the organization on employee performance, to indicate the significance of the impact of employee performance on satisfaction and whether the organization can mediate employee job satisfaction. This type of research uses the census method for Mitra Swalayan Kartasura employees. This research uses qualitative data and quantitative data. Meanwhile, the data source uses primary data and secondary data. The population is all employees of Mitra Swalayan Kartasura who assess 85 employees. The sample in this study were 85 employees with the census method. The data analysis technique used multiple regression test, t test, F test, indirect effect test, path analysis and coefficient of determination. The results of the study indicate that job satisfaction can have a positive and significant effect on organizational commitment, there is no positive and significant influence between organizational commitment on employee performance, job satisfaction can have a positive and significant effect on employee performance and in this study it cannot prove that organizational commitment. mediate job satisfaction on employee performance.